A systematic review of contract farming, and its impact on broiler producers in Lebanon - Kozhaya, Rodrique (Open Science Journal, 2020)
This Thesis has been realized within the agribusiness sector and experiments the Transaction Cost Theory a branch of the New Institutional Economy which explain market failure caused by many factors. Transaction costs are associated with carrying a transaction between buyers and sellers. This study has been conducted between 2014 and 2017; and has collected data from 11 broiler producers in Jezzine, Lebanon, about: Production costs, capital investment, revenues, land tenure, access to infrastructure, and information about the contract. The propensity score matching method is used to compare the effect of participating in contract farming and to solve the hypotheses, which say: There is a positive relationship between contract farming and the economic benefits of broiler producers and the development of the broiler sector in Jezzine District. Findings from farmer’s interviews indicated that sustainability, guaranteed price, risk reduction, credit facilities and technical aids are the main reasons for signing a contract. In contrast, Farmers have expressed problems concerning the contractors’ responsibilities such as delay in payment and delivery. Also, when prices are high, it was argued that farmers were selling the products in the open market.